First-in-human study of naporafenib (LXH254) with or without spartalizumab in adult patients with advanced solid tumors harboring MAPK signaling pathway alterations - Janku, Filip; Kim, Tae Min; Iyer, Gopakumar; Spreafico, Anna; Elez, Elena; de Jonge, Maja; Yamamoto, Noboru; van der Wekken, Anthonie J.; Ascierto, Paolo Antonio; Maur, Michela; Marmé, Frederik; Kiladjian, Jean-Jacques; et al. (European journal of cancer, 2024)
Background: We investigated naporafenib (LXH254), a pan-RAF kinase inhibitor, with or without spartalizumab, in patients with advanced solid tumors harboring MAPK pathway alterations. Methods: This first-in-human phase 1 study had two dose-escalation arms: single-agent naporafenib (starting at 100 mg once-daily [QD]) and naporafenib (starting at the recommended dose/regimen)/spartalizumab (400 mg every 4 weeks). The naporafenib/spartalizumab dose-expansion part enrolled patients with KRAS-mutated nonsmall cell lung cancer (NSCLC) and NRAS-mutated melanoma. The primary objectives were to establish the maximum tolerated doses (MTD)/recommended doses for expansion (RDE) and evaluate tolerability and safety. Results: A total of 142 patients were included in the naporafenib dose-escalation (n = 87), naporafenib/spartalizumab dose-escalation (n = 12) and naporafenib/spartalizumab dose-expansion (n = 43) arms. The MTD/ RDE of naporafenib was 600 mg twice-daily (BID). In naporafenib escalation, five patients experienced 7 doselimiting toxicities: decreased platelet count (1200 mg QD); neuralgia, maculopapular rash, pruritus (600 mg BID); increased blood bilirubin, hyponatremia, peripheral sensory neuropathy (800 mg BID). No DLTs occurred in the naporafenib/spartalizumab arm: the RDE was established at 400 mg BID. The most common treatment related adverse events were rash and dermatitis acneiform (each 24.1%; naporafenib), nausea and pruritus (each 33.3%; naporafenib/spartalizumab; escalation) and rash (39.5%; naporafenib/spartalizumab; expansion). Naporafenib reduced DUSP6 expression in tumors. Two partial responses (PRs) occurred in naporafenib esca-lation, and 1 complete response and 3 PRs in the naporafenib/spartalizumab NRAS-mutated melanoma and KRAS-mutated NSCLC arms, respectively. Conclusions: Naporafenib, with or without spartalizumab, showed an acceptable safety profile, pharmacodynamic activity and limited antitumor activity. Additional naporafenib combination therapies are currently under investigation.
Online veröffentlicht: 20. November 2023
Gesehen am 02.08.2024